EFFECTS OF CHARRING ON THE CARBON ISOTOPIC COMPOSITION OF GRASS (POACEAE) EPIDERMIS - Beuning K.R.M.; Scott J.E. (My University, 2002)
Charred modern grass epidermis preserves the carbon isotopic composition of the parent plant photosynthetic pathway. Fifty-nine modern grasses and sedges were collected in lowland western Uganda. All charred epidermal samples from C4 grasses or sedges preserve a carbon isotopic value within the range typical for C4 plants (−17 to −10‰), and charred epidermal fragments from C3 plants have carbon isotopic values between −30 and −26‰. The process of charring results in a slightly enriched carbon isotopic signature (−11.9‰ mean charred value as compared to −12.8‰ mean unaltered grass tissue value). δ13C measurements of replicate samples from the same plant vary within 1–2‰, yet all values for the same plant stay within the expected values for the photosynthetic pathway of the plant. δ13C measurements on >180-μm charred grass epidermal fragments extracted from surface sediment samples from three lakes on the lowland western Ugandan landscape confirm the predominant lowland C4 grass input (δ13C=−16 to −19‰). These results demonstrate the utility of using carbon isotopic analysis of charred grass epidermis to reconstruct C3 vs. C4 grassland assemblages on the landscape. Furthermore, such downcore δ13C profiles can be used to highlight key zones of C3 vs. C4 grass change for which taxonomic analysis of fossil grass epidermis could provide more detailed information regarding grassland community composition.